Potential Rice Straw as Biofertilizer in Rice (Oryza sativa L.) in Tidal Soils - Neni Marlina; Ida Aryani; Khodijah Khodijah; Marlina Marlina; Joni Phillep Rompas; Deny Yulianto; Haperidah Nunilahwati; Nurul Husna; Cik Aluyah (Journal of Global Sustainable Agriculture, 2022)
Rice productivity in tidal lands can be achieved by using local resources, including managing rice straw as a biological organic fertilizer (POH). The biological organic could be used with ingredients rice straw: chicken manure: Azospirillum bacteria, and Phosphate Solvent Bacteria (6:4:1). These can increase soil fertility, nitrogen, and phosphorus and potassium nutrients through the activity of microorganisms (Azospirillum and Phosphate Solvent Bacteria). This study aims to obtain the right dose of POH to increase rice production in tidal soils. This research was carried out in an experimental garden, using tidal soil media type C overflow from Banyuurip Village, Banyuasin Regency. Testing using field experiments. The layout used a Randomized Group Design with 4 treatments repeated 6 times, namely POH (D) doses: 0 kg/ha (D0), 200 kg/ha (D1), 400 kg/ha (D2), 600 kg/ha (D3). The best results were found in using POH with a dose of 600 kg/ha, which was 41.67 g / plant and increased production by 87.96% compared to without POH.